2-Hydroxy-6-[(2-Methoxyphenyl)aminomethylene]cyclohexa-2,4-Dienone - Sahin, O.; Büyuk̈güngör, O.; Albayrak, Ç.; Odaba̧soǧlu, M. (Int. Union Crystallography, 2006)
The molecule of the title compound, C14H13NO 3, adopts the keto-amine tautomeric form. An intramolecular N-H⋯O hydrogen bond dictates the essentially planar molecular geometry; the two benzene rings make a dihedral angle of 7.93 (7)°. The crystal packing is stabilized by intermolecular O-H⋯O and C-H⋯O hydrogen bonds. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.